PPh Pasal 21 Ditunjang atau Ditanggung - Lusy Suprajadi (Bina Ekonomi, 1999)
Income tax art. 21 is a witholding income tax law based on any kind of income, received by a person. Income tax art. 21 is regulated in detail by Director General of Taxes Decree (Keputusan Direktur Jenderal Pajak) No.KEP-281/PJ/1998 dated 28 December 1998. This paper will compare how 'tax income art 21 allowance' or tax income art 21 paid by the employee/employer can influence the employee (take home pay), the employer (income statement) and the government (state income).